The Second Treaty of Erzurum and the Ottoman-Qajar border problem and their influence on Blbas (1847-1880) (Raparin Journal of Humanities (RJH), 2024)
Blbas was a tribal union and consisted of Mamash, Mangur, Piran, San, Ramk, Hormzyar and Gowrk tribes in the nineteenth century. They mostly lived a semi-nomadic life in Garmian and the deserted areas caused not comply with the regulations and restrictions of the Ottoman and Qajar states. As their long-standing tradition with the drop in temperatures and getting cold, they were heading to the hot areas of the Ottoman State (South of Kurdistan), and with the rise in temperatures and decrease in the pasture, they were moving to the highlands of Qajar state (East of Kurdistan). The migration and movement of the Blbas tribes began to cross the border and violated the provisions of the peace treaties between them, so the two countries accused the Blbas tribes of being the source of instability and crossing borders. In their treaty and border protocols, both countries have consistently referred directly or indirectly to the Blbas, they planned to oblige the tribes to take orders from the central governments and be inhabited in a specific area.     The Ottoman and Qajar states used different techniques to abide the Blbas tribes such as; joint military attacks, tricks and deceptions, and creating conflicts among them. All this reveals the fact that the tribes of Blbas never gave up while they have been located in an important geopolitical position. Their courage and lack of surrender to the continuous ambitions of both states, they have always lived in an unstable and chaotic situation. They have become the major issue of the treaties and documents of the time when the Ottoman and Qajar states had a decisive impact on the history of the events in the region.